Efficient Fenton-like treatment of high-concentration chlorophenol wastewater catalysed by Cu-Doped SBA-15 mesoporous silica. (10th October 2021) - Hu, Huanting; Miao, Kangkang; Luo, Xiaolin; Guo, Sifan; Yuan, Xueqin; Pei, Fei; Qian, Huaming; Feng, Guodong
Abstract: Effective treatment for industrial wastewater that contains high concentration of chlorophenols is urgent and indispensable for environmental governance and human health due to their nonbiodegradable, carcinogenic and cytotoxic properties. Four kinds of Cu-containing mesoporous silica materials were utilized to catalyse Fenton-like treatment of high-concentration chlorophenols wastewater (1.0 g L −1 ). All of chlorophenols in various water matrices could be oxidatively decomposed in 35 min with the catalysis of Cu-doped SBA-15. Cu-doped SBA-15 with a Cu/Si molar ratio of 0.133 had the best catalytic activity in the oxidative degradation of 4-chlorophenol with an apparent reaction rate constant of 0.170 min −1 which was 1.3–3.6 times higher than those with other Cu-containing catalysts. After 300 min reaction, total organic carbon content of 4-chlorophenol solution declined continuously to 23.8% with an advisable utilization efficiency of H2 O2 of 26.5%–68.4%. Electron spin resonance tests and quenching experiments demonstrated that Cu-doped SBA-15 had a selective catalytic activity in the decomposition of H2 O2 into hydroxyl radicals which dominated the degradation of chlorophenols in wastewater. The redox of Cu(II)/Cu(I) in Cu-doped SBA-15 occurred efficiently, which could be attributed to chemical adsorption and electron transformation of organic molecular fragments onto Lewis acidic sites formed by the incorporation of Cu 2+ ions in SBA-15. The biological toxicity of the treated 4-CP wastewater declined significantly in comparison with that of the original wastewater. Our work provided an effective way of the heterogeneous treatment of high-concentration chlorophenol wastewater. Graphical abstract: Image 1 Highlights: A modified free-radical route was applied to fabricate Cu-doped SBA-15 with Cu/Si molar ratio as 0.133. Cu-doped SBA-15 exhibited advisable catalytic activity in the Fenton-like degradation of 4-CP. Organic radical fragments generated in the Fenton-like reactions facilitate the redox of Cu(II)/Cu(I). A possible reaction pathway for the decomposition of 4-CP was proposed according to GC–MS data.